Septic abortion complicated by infective endocarditis, mitral valve vegetation, and septic and reactive arthritis: A case report - Raina Kishan; Shaun Wesley; George Barnett; Robert P. Kauffman (Elsevier, 2022)
Background: Septic abortion with multisystem involvement is associated with significant morbidity and mortality. Access to care and legalization of abortion have greatly diminished the incidence of serious sequelae worldwide. Two complications, infective endocarditis and septic arthritis, are rarely encountered in contemporary practice. Case: A 30-year-old woman developed infective endocarditis, septic arthritis, and reactive arthritis concurrently one week after undergoing dilation and curettage for an incomplete abortion with perioperative administration of doxycycline. She required systemic antibiotics, drainage and debridement of her right ankle, and a robotic-assisted mitral valve replacement due to septic vegetation. Conclusion: Septic abortion with life-threatening systemic complications is rarely encountered in modern practice. Prompt surgical uterine evacuation and broad-spectrum antibiotics are indicated to prevent systemic complications. Multispecialty consultation is usually required when endocarditis, arthritis, and other systemic complications are encountered.